Two new flat mite species of the genus Aegyptobia Sayed, 1950 (Acari: Trombidiformes: Tenuipalpidae) from Iran - Farzan, Sadegh; Asadi, Mahdieh; Ueckermann, Edward; Shirvani, Asghar (Zootaxa, 2012)
Two new flat mite species (Acari: Trombidiformes: Tenuipalpidae) are described: Aegyptobia jiroftiensis sp. nov. from Convolvulus polygonum (Convolvulaceae) and Aegyptobia hormozgani sp. nov. from Artemisia siberia (Asteraceae).